Serum 14-3-3η is a novel marker that complements current serological measurements to enhance detection of patients with rheumatoid arthritis - Maksymowych, Walter P; Naides, Stanley J; Bykerk, Vivian; Siminovitch, Katherine A; van Schaardenburg, Dirkjan; Boers, Maarten; Landewé, Robert; van der Heijde, Désirée; Tak, Paul-P; Genovese, Mark C; Weinblatt, Michael E; Keystone, Edward C; et al. (Journal of rheumatology, 2014)
Serum 14-3-3η is a novel joint-derived proinflammatory mediator implicated in the pathogenesis of rheumatoid arthritis (RA). In our study, we assessed the diagnostic utility of 14-3-3η and its association with standard clinical and serological measures. A quantitative ELISA was used to assess 14-3-3η levels. Early (n=99) and established patients with RA (n=135) were compared to all controls (n=385), including healthy subjects (n=189). The sensitivity, specificity, positive and negative predictive values of 14-3-3η, and the likelihood ratios (LR) for RA were determined through receiver-operator curve analysis. The incremental value of adding 14-3-3η to anticitrullinated protein antibody (ACPA) and rheumatoid factor (RF) in diagnosing early and established RA was assessed. Serum 14-3-3η differentiated established patients with RA from healthy individuals and all controls (p<0.0001). A serum 14-3-3η cutoff of ≥0.19 ng/ml delivered a sensitivity and specificity of 77% and 93%, respectively, with corresponding LR positivity of 10.4. At this cutoff in early RA, 64% of patients with early RA were positive for 14-3-3η, with a corresponding specificity of 93% (LR+ of 8.6), while 59% and 57% were positive for ACPA or RF, respectively. When ACPA, RF, and 14-3-3η positivity were used in combination, 77 of the 99 patients (78%) with early RA were positive for any 1 of the 3 markers. Serum 14-3-3η did not correlate with C-reactive protein, erythrocyte sedimentation rate, or Disease Activity Score, but patients who were 14-3-3η-positive had significantly worse disease. Serum 14-3-3η is a novel RA mechanistic marker that is highly specific, associated with worse disease, and complements current markers, enabling a more accurate diagnosis of RA.